2017
DOI: 10.1155/2017/3079141
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Avascular Zone in Normal Tension Glaucoma Measured by Optical Coherence Tomography Angiography

Abstract: Aim To measure diameter of foveal avascular zone (FAZ), FAZ area, and vessel density using Optical Coherence Tomography Angiography (OCT-A) in patients with normal tension glaucoma (NTG) and to establish the possible role of OCT-A in diagnosis and follow-up of patients with NTG. Methods Twenty-one eyes of 21 patients with NTG and 30 eyes of 30 healthy subjects underwent complete ophthalmic examination as well as OCT-A on ZEISS AngioPlex. 3 × 3 macula scans were used to measure vertical, horizontal, and maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 30 publications
4
21
0
2
Order By: Relevance
“…On the other hand, the grid-based analysis revealed that the progressed HTG group showed decreased VD in both the superior and deep retinal layers, while the progressed NTG group exhibited a more universal vascular defect in the deep layer compared to the control group. The FAZ in the progressed NTG group was larger than that in the control group, similar to a previous study [30], except the larger FAZ in the current study occurred before significant NTG development. Since circulation is an important factor for the occurrence and progression of NTG, rather than prominent high IOP [31, 32], more extensive vascular defects could be possible for impending NTG compared to HTG.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, the grid-based analysis revealed that the progressed HTG group showed decreased VD in both the superior and deep retinal layers, while the progressed NTG group exhibited a more universal vascular defect in the deep layer compared to the control group. The FAZ in the progressed NTG group was larger than that in the control group, similar to a previous study [30], except the larger FAZ in the current study occurred before significant NTG development. Since circulation is an important factor for the occurrence and progression of NTG, rather than prominent high IOP [31, 32], more extensive vascular defects could be possible for impending NTG compared to HTG.…”
Section: Discussionsupporting
confidence: 90%
“…In the study written by Moghimi et al [10], the lower baseline macular and peripapillary VD were related to faster disease deterioration in mild to moderate primary HTG, whereas the results of the current study from the progressed HTG group reflect worse macular circulation compared to those simple cases before the diagnosis of significant glaucoma. Nevertheless, the relationship between SmVD as well as DmVD and structural damage in progressed NTG patients has rarely been reported elsewhere, and the association between basal FAZ area and VF defects in these patients further supports the previous concept that a larger FAZ was found in NTG [30]. These results further support that vascular abnormalities may be the main cause of glaucoma neuropathy in NTG, especially in progressed cases, which has been proven in both animal and human research [34, 35].…”
Section: Discussionsupporting
confidence: 84%
“…Another fact that should be highlighted is the occurrence of variation of retinal capillary density and age-related FAZ dimensions [12,13], highlighting the importance of new findings from OCT-A. This has been reported in other ischemic diseases, such as diabetic retinopathies [11,14,18,19] and sickle cell disease [20,21], in addition to glaucoma [22], with possible involvement at the level of the deep plexus, in addition to the histological variation found in this plexus, with greater distancing of the fovea and increased dimensions compared to the superficial plexus [23]. However, such enlargement is not easily interpreted, since there is variation in the size of this area also in the general population, since in a single individual this measurement can usually be large or abnormally increased.…”
Section: Discussionmentioning
confidence: 83%
“…At the same time, patients with NTG have a larger FAZ area and decreased peripheral vascular density. The OCTA technology has been used to further demonstrate that NTG is an ischemic disease characterized by vascular dysfunction [32] . In the present study, FAZ significantly changed in the early stage of APACG, indicating that it was a sensitive indicator of APACG-induced changes in retinal circulation.…”
Section: Discussionmentioning
confidence: 99%